Research is a craft: research like a craft - Gautam, Sahadev (Innovative Research Journal, 2025)
Research perspective and research practice are only possible through the practice of good dedication, where there will be a better expected outcome. Research craft is the basic part of the overall ground of the research, and this is like a bunch of questions for researchers. In the article, craft is the core concern for the analysis. Modern academic and non-academic society is run under the concept of good research and participatory methods practices. The major aim of the article is to focus research as discourse from a critical focus point and its rhetorical realities. In this way, research and craft are synonymously used. Based on secondary data, the thematic analysis method is used to shape this article. From the analysis, the circumference of the research discourse has become ubiquitous in modern social science research perspectives. Discourse of research and discourse in craft in the contemporary world have different notations described by different perspectives.